Online activity duration management system for manufacturing company - Soh, Hui Gian; Kasim, Shahreen; Hassan, Rohayanti; Zakaria, Zalmiyah; Mahdin, Hairulnizam; Ramli, Azizul Azhar; Md Fudzee, Mohd Farhan; Salamat, Mohamad Aizi (Zibeline International Publishing, 2019)
The researcher of Asian Composites Manufacturing Sdn. Bhd. (ACM) are currently doing a research on how to reduce waste within all processes in an activity duration of the production, in order to increase profit for the company. Currently, the duration of the activity processes was recorded by manual procedure in paper-based form which are prone to many problems. At the same time, it lacks in real-time feedback between the researcher and the staff of ACM. To overcome these problems, the Online Activity Duration Management System (OADMS) is proposed. This system will computerize the manual procedure. It is provided in a web-based environment. The OADMS system is developed by using the waterfall system development methodology, while the programming languages are using Hypertext Markup Language (HTML), Hypertext Preprocessor (PHP), Structured Query Language (SQL) and JavaScript. The OADMS provided a systematic activity duration management for staff of ACM and eased the works of researcher in analyzing the processes and providing feedbacks for improvements of the activity duration. By, providing a computerized solution, it is concluded that the activity duration management is more systematic and precise.